Equity, diversity, and inclusion at the Global Alliance for Genomics and Health - Neerjah Skantharajah; Shakuntala Baichoo; Tiffany F. Boughtwood; Esmeralda Casas-Silva; Subhashini Chandrasekharan; Sanjay M. Dave; Khalid A. Fakhro; Aida B. Falcon de Vargas; Sylvia S. Gayle; Vivek K. Gupta; Rachele Hendricks-Sturrup; Ashley E. Hobb; et al. (Cell Genomics, 2023)
Summary: A lack of diversity in genomics for health continues to hinder equitable leadership and access to precision medicine approaches for underrepresented populations. To avoid perpetuating biases within the genomics workforce and genomic data collection practices, equity, diversity, and inclusion (EDI) must be addressed. This paper documents the journey taken by the Global Alliance for Genomics and Health (a genomics-based standard-setting and policy-framing organization) to create a more equitable, diverse, and inclusive environment for its standards and members. Initial steps include the creation of two groups: the Equity, Diversity, and Inclusion Advisory Group and the Regulatory and Ethics Diversity Group. Following a framework that we call “Reflected in our Teams, Reflected in our Standards,” both groups address EDI at different stages in their policy development process.